Curcumin prevents chronic intermittent hypoxia-induced myocardial injury. (June 2020) - Moulin, Sophie; Arnaud, Claire; Bouyon, Sophie; Pépin, Jean-Louis; Godin-Ribuot, Diane; Belaidi, Elise
Background: Chronic intermittent hypoxia (IH), the hallmark feature of obstructive sleep apnoea syndrome, contributes to infarct size enhancement after myocardial ischemia–reperfusion (I/R). Curcumin (Curc), the natural pigment of Curcuma longa, has been demonstrated to be beneficial in the context of myocardial injury. In this study, we assessed the effects of Curc on the maladaptive cardiac response to IH, and particularly on IH-induced hypoxia inducible factor-1 (HIF-1) expression, oxidative stress, inflammation, endoplasmic reticulum (ER) stress and apoptosis. Methods: Swiss/SV129 mice were exposed to normoxia or IH (21–5% FiO2, 60 s cycles, 8 h per day, for 21 days) and treated orally with Curc (100 mg kg −1 day −1, oral gavage) or its vehicle. Mice were then either euthanised for heart sampling in order to perform biochemical and histological analysis, or subjected to an in vivo ischemia-reperfusion protocol in order to measure infarct size. Results: IH increased nuclear HIF-1α expression and superoxide anion (O2 .– ) production as well as nuclear factor kappa B (NF-kB) p65, glucose-regulated protein (Grp78) and C/EBP homologous protein (CHOP) expression. IH also induced apoptosis and increased infarct size after I/R . The IH-induced HIF-1 activation, oxidative stress, inflammation, ER stress and apoptosis were abolished by chronic Curc treatment. Curc also significantly decreased infarct size only in mice exposed to IH. Conclusion: Curc prevents IH-induced myocardial cell death signalling. Curc might be used as a combined therapy with continuous positive airway pressure in sleep apnoea patients with high cardiovascular risk.